Analisis Laju Sedimen Berdasarkan Data Unsteady Flow Real Time Dengan HEC-RAS di DAS Bomo Banyuwangi - Syafaat, Habib Marjun; Prasetyo, Yohanes Pracoyo Widi; Sujatmiko, Heri; Purnomo, Dimas Aji; Erwanto, Zulis (Indonesian Society of Applied Science, 2025)
The 2018 flash flood in Banyuwangi Regency highlighted the role of sedimentation in increasing disaster risks. This study aims to analyze sedimentation rates based on real-time unsteady flow data during the rainy and dry seasons, understand the relationship between unsteady flow and sedimentation, and evaluate the role of HEC-RAS in mitigating sedimentation-related risks. Hydrometric measurements were conducted in real-time over seven days in both seasons. Data were analyzed using HEC-RAS and validated using the Mean Absolute Error (MAE) method of bathymetric measurements. The results show that sedimentation rates were higher during the rainy season (2.77 m³/day) compared to the dry season (1.33 m³/day) due to increased discharge and flow velocity. Flow velocity correlates more strongly with sedimentation than discharge, with regression values of 0.8257 in the dry season and 0.4072 in the rainy season. Flood modeling with HEC-RAS indicates that sedimentation increases flood risks, particularly in downstream areas. Therefore, mitigation measures such as river normalization, embankment construction, drainage optimization, and upstream soil conservation are necessary. These findings also support early warning systems to enhance community preparedness for sedimentation-induced floods.